Pulse wave analysis measurements: important, underestimated and undervalued parameters in cardiovascular health problems - Claessens, Philip Jan; Peeters, Ruth; Claessens, Louis; Claessens, Christophe; Claessens, Jan; Claessens, Philip Maria (Frontiers in Cardiovascular Medicine, 2023)
Background Central aortic stiffness is established as a reliable measure of cardiovascular disease. While pulse wave velocity (PWV) analysis measures arterial distensibility, risk profile of cardiovascular diseases can be expanded with following pulse wave analysis measurements: central aortic systolic blood pressure (CABPS), central aortic pulse pressure (CAPP), central aortic reflection magnitude (CARM), central aortic augmented pressure (CAAP) and central aortic augmentation index (CAAIx). The aim of this study is to evaluate the clinical usefulness and importance of pulse wave analysis measurements in specific cardiovascular conditions and diseases, both in term of diagnosis and therapeutic monitoring. Methods One thousand sixty-six subjects were included. According to age bracket, four cohorts were investigated—healthy subjects (NL), hypertensive patients (HP), ischemic heart disease (IHD) and valvular heart disease (VHD) patients. Arterial stiffness was analyzed through Sphygmocor XCEL Central Blood Pressure Measurement System and Sphygmocor XCEL PWV Measurement System. Furthermore we observed the pulse wave analysis measurements of 14 patients with diagnose of ADHD who were referred by a child psychiatrist, in order to investigate the initiation of methylphenidate treatment. Results Statistically significant differences were found between NL and HP cohorts, across almost all age brackets, regarding pulse wave analysis measurements. In the risk stratification of arterial stiffness hypertension and especially central aortic blood pressure systolic (CABPS) seems a determining factor. Pulse wave analysis measurements for IHD and VHD cohort comparisons with NL counterparts, revealed non- statistically significant variations. Elevated CAAP, CAAIx and CARM within the youngest age group (0–10 years) in attention-deficit-hyperactivity-disorder (ADHD) patients warrant attention. Conclusions Following such investigations, CABPS appears as a robust predominant factor in problems of arterial stiffness. Pulse wave analysis and PWV are important parameters in the evaluation and monitoring of arterial hypertension and cardiovascular diseases. There is a hypothesis that CAAP could be an important and even decisive parameter in the diagnosis of ADHD. Further investigation needed.